2020
DOI: 10.1097/qai.0000000000002455
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Frailty Tools in Mortality Prediction of Middle-Aged Adults With HIV

Abstract: Background: Frailty and physical function impairments occur at an earlier than expected age in people with HIV (PWH). The goal of this study was to determine which tools or combination of tools assessing frailty/physical function were most predictive of mortality in a middle-aged population of PWH.Methods: Using electronic health records, we determined survival, death, or loss-to-follow-up for 395 PWH, aged 45-65 originally enrolled in a 2009-2010 cross-sectional cohort study. The predictive accuracy of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A retrospective study has shown that poor physical function, falls and frailty are all predictive of mortality in middle-aged people living with HIV [68]. A systematic review noted that the predominant factors contributing to poorer physical function include HIV severity, chronic inflammation and oxidative stress, peripheral and central nervous system dysfunction and the presence of comorbidities [69 ▪▪ ].…”
Section: Physical Function and Rehabilitationmentioning
confidence: 99%
“…A retrospective study has shown that poor physical function, falls and frailty are all predictive of mortality in middle-aged people living with HIV [68]. A systematic review noted that the predominant factors contributing to poorer physical function include HIV severity, chronic inflammation and oxidative stress, peripheral and central nervous system dysfunction and the presence of comorbidities [69 ▪▪ ].…”
Section: Physical Function and Rehabilitationmentioning
confidence: 99%
“…Physical frailty is a clinical syndrome defined by five criteria—shrinking, weakness, poor endurance and energy, slowness, and low physical activity level—in which the whole is more than the sum of the parts in terms of predicting adverse health outcomes [ 12 ]. Frailty is prevalent in the older adults with HIV, is associated with mortality and is potentially reversible [ 13 15 ].Frailty is starting to be proposed as a clinical marker of biological age [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, measures of physical performance, including gait speed and SPPB, correlated with even more health outcome measures (Table S4) . These parameters had also been shown to predict mortality among PLWH [ 43 , 44 ]. Our findings, therefore, supported AWGS‐2019 in including the presence of either muscle strength or physical performance in the definition of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%